Track reconstruction in the BESⅢ muon counter - 梁羽铁 刘坤 尤郑昀 冒亚军 李卫东 边渐鸣 曹国富 曹学香 陈申见 邓子艳 傅成栋 高原宁 韩磊 韩少卿 何康林 何苗 胡继峰 胡小为 黄彬 黄性涛 贾卢魁 季晓斌 李海波 刘北江 刘春秀 刘怀民 刘颖 刘勇 罗涛 吕绮雯 马秋梅 马想 毛泽普 莫晓虎 宁飞鹏 平荣刚 邱进发 宋文博 孙胜森 孙晓东 孙永昭 田浩来 王纪科 王亮亮 文硕频 伍灵慧 吴智 谢宇广 徐敏 言杰 严亮 姚剑 苑长征 袁野 张长春 张建勇 张雷 张学尧 张瑶 郑阳恒 朱永生 邹佳恒 (Chinese physics C, 2009)
The reconstruction algorithm for BESⅢ Muon Counter, MucRecAlg, is developed with the objectoriented language C＋＋ in BESⅢ offine software environment. MucRecAlg consists of the following functions：to find track seeds either from extrapolation of tracks in the main drift chamber or from the fired strips in muon counter, to select fired strips associated to the candidate tracks, to fit the candidate tracks with a linear or quadratic function and to calculate other parameters of the tracks for muon identification. Monte Carlo samples are generated to check the performance of the reconstruction package, such as reconstruction effciency, muon remaining rate and pion rejection rate, etc. The preliminary results show that the pion rejection rate is around 3%—4% while the muon remaining rate is better than 90% in 0.4—1.6 GeV/c momentum region, which meets the requirement as shown in the design report.